Uncovering metabolite changes in rice leaves (Oryza sativa L.) during vegetative stages using ethanolic extract analysis based on gas chromatography-mass spectrometry - Nguyen, Thi-To-Uyen; Nguyen, Phu-Tho; Pham, Minh-Nhut Pham; Nguyen, Thi-Phuong-Thao; Tran, Thanh-Thai; Nguyen, Huu-Thanh; Nguyen, Thi-Tho (Agriculture and Natural Resources, 2026)
Importance of the work: This research contributes to understanding rice physiology and emphasizes the potential for utilizing metabolomic data in breeding programs aimed at enhancing crop resilience and yield. Objectives: To investigate the metabolite profiles of rice leaves and to elucidate the catabolic pathway of chlorophyll during critical growth stages. Materials and Methods: Two rice varieties, IR50404 (IR504) and Huyet Rong (HRO), were examined at 3 wk and 5 wk of growth to elucidate the changes in key metabolites using gas chromatography-mass spectrometry analysis. The total chlorophyll contents of rice leaves were measured to determine the shift in metabolite pathways. Results: There were significant differences in the chlorophyll content, with both varieties having higher levels at 3 wk than at 5 wk. The profiling revealed that IR504 contained a greater number of metabolites than HRO at both time points. Notably, phytol and bis(2-ethylhexyl) phthalate (DEHP) were predominant compounds, with the phytol levels notably increasing in HRO by week 5. Additionally, there were metabolic shifts in the volatile organic compounds, with an increase in diterpenoids and a decrease in phthalate esters as the plants matured. Based on the results, the study proposed the metabolic pathway of chlorophyll degradation to produce important compounds (phytol, vitamin E and fatty acid derivatives) in rice leaves. Main finding: Overall, the findings underscored the dynamic nature of rice leaf metabolism and provided insights into the biochemical adaptations that occur during critical growth stages.